(untitled) (Archives of Criminology, 1969)
1. Problems related to juvenile delinquency have always been a subject of vivid interest of both scientific circles and the community at large. Consequently, juvenile delinquency has probably become a criminological problem given a most profound consideration and any studies which concern that type of delinquency get a vivid response also outside a nanow expert community. Among such studies, modest though and certainly not foreground place is occupied by analyses of statistical materials. Since the results of the analyses mentioned “grow old” much quicker than do the results of individual, more advanced studies, it seems purposeful, therefore, to make efforts in the direction of bringing them more up-to-date. At least one problem seems to demand such up-dating most specificaliy, i.e., the problem of the assessment of the general data obtained from the police and judicary statistics since such data can be one of juvenile the bases for determining the extent of delinquency. Having considered that within the meaning of the criminal law juveniles and adults are, in an arbitrary manner, demarcated merely by age limit (before or after 17 years of age at the moment an offence was committed) whose artificiality is somehow shocking from the criminological point of view, it seemed also advisable to-include in this study other questions related to the extent of delinquency of young adults as well as to consider its situation against the background of the adult population. Another group of questions discussed is connected with the structure of delinquency; also special attention has been paid to questions of place the suspects or those found guilty (and young adults, too) herd among the total numbers of suspected or convicted adults. Finally, there is the third group of questions given special consideration in this study, namely the educative and correctional means adjudicated upon juveniles. Although there is a good deal of information on that particular topic as well as more or less detailed papers concerning the analysis of these kind of data nevertheless the material in question has not so far been analysed in terms of an adequately long period of time which would permit to seize certain clearly-cut tendencies in adjudication of particular kinds of means, especially against the background of various fluctuations of numbers of juveniles appearing in the court. In that chapter of this essay, the studies have been considerably extended to include 1951-1967 instead of 1961-1967 as in the remaining ones. 2. 1. In analysing various kinds of contexts in which, particular authors mention the range of juvenile delinquency - especially when they are alarmed by its increase or whenever they are pleased to note its stabilization or decrease - one may easily see that the authors usually have different things in mind. Sometimes their opinions are based on more and sometimes on less founded assumptions or estimations concerning the number of juvenile offenders themselves, sometimes on the number of their offences, the importance of such deeds or their frequency rate, the degree of social depravity in juveniles appearing in courts, and finally, together - on a series of the abovementioned instances (and also on ones not mentioned there). Anyway, always where one or another adequately justified opinion on the extent of juvenile delinquency is found, the reader is able either to know at once or to trace back what in ęach particular case was the measure of the extent in question. The purpose of the present study is to show different ways for the determination of the detected extent of juvenile delinquency and to present certain groups of data which might serve as the most appropriate criteria for the evaluation of the dimensions of delinquency; furthermore, the intention of the present author is to show that at least some of the criteria are by no means of competitive nature but that they rather permit us to grasp different aspects of the problem of juvenile delinquency. It would be difficult therefore to forejudge about the superiority of one criterion over another as they concern different aspects of the samę problem and as such may have a different impact for our analyses, depedent on the line of our research. 2. A relatively large number of juveniles found among the total number of suspected or convicted individuals may sometimes incline us towards making certain far-reaching statements concerning the extent of juvenile delinquency. Some people hold the opinion that whenever juveniles (or sometimes juveniles and young adults) constituted a considerable portion of the total number of offenders, the range of their delinquency should be recognized as significant, if only on account of their share in delinquency. The author is doubtful about the rightfulness of such an opinion if it were only for a specific character of the juvenile delinquency structure, the importance of offences or also for other than in the case of adults, aims of prosecution (in the broadest meaning of that word). It does not mean, however, that it would not be worth while what is the place the known now in Poland juvenile offenders hold among the total number of individuals convicted. In 1961-1967, juveniles under 13 years of age constituted merely 2-3 per cent of the total number of individuals convicted (similar percentage was noted in the last decade 1951-1960). Together with 13-16 year-old offenders, the juveniles constituted only a group of several per cent - and in recent years - a dozen-or-so per cent group. The number of very young and young that had been found guilty (i.e., juveniles and young adults) was bigger but stin did not exceed 1/5-¼ of the total number of the individuals convicted out of which half were almost 30 or older at the time they committed the offences. It is fitting to note at this point that in a number of countries, persons under 21 years of age constitute 1/2 and sometimes 2/3 of the total number of the individuals convicted or suspected. It may then be said that from the point of view of a relative quantity of juveniles found in the total number of the individuals convicted, that juvenile delinquency in poland may still be estimated as a highly moderate one. 3. Out of all the available methods that can be employed for the evaluation of the extent of juvenile delinquency the simplest one is that which bases on the statistical data concerning the number of juveniles found guilty, or more broadly juvenile adjudgments, or even still more broadly - the number of cases in which a juvenile was suspected of an offence. The limitations involved in the use of such a criterion are quite evident since in applying such a criterion we fail to consider any consequences of the fact that the number of adjudgements or findings of guilt is hardly synonymous with the number of juveniles adjudicated or found guilty (which could after all be justified), but - and this is less acceptable - such a number does not bear any relation to the wider population - events or individuals - against whose background it occurs. However, from one point of view this criterion is important, namely it provides relatively accurate information about one of the quantitative aspects of risks faced by the police and the court of law, involved with the conduct of proceedings and with the adjudication upon the offences committed by juveniles. This criterion becomes particularly important whenever we tackle with organizational problems of courts for juveniles, or the needs for staff or institutions. For the last seven years, the total number of adjudgements increased from about 47 thousand to 71 thousand (i.e. by 52 pet cent). As compared with 1951 (abo 26 thousand), the total number of the adjudgements in 1967 was almost threefold. Close to the latter was the number of juveniles suspected by the police of offending the law (for the last four years past, it was 53 to 70 thousand a year). Out of the total number of the adjudgements, the findings of guilt held similar place (54 to 56 per cent) slightly lower than in 1951-1960 when the proportion was about 56 to 61 per cent. In the seven-year period discussed, the proportion of discontinuations of legal proceedings evidently increased: at the present moment, 33 to 34 per cent of juvenile cases are dismissed, in 1951-1960 on the other hand, the proportion having been 20 to 30 per cent. Various categories of juveniles are involved therein. Acquittals are a particular category of adjudgements; the absolute number of acquittals was on an approximate level (2,300-2,800) but owing to the simultaneous increase in the total number of adjudgements, the percentage of acquittals decreased to 4 per cent. Perhaps it is worth while remembering that acquittals were as many as 11 per cent of adjudgements in 1951, but already in 1952 and onwards, the proportion had been stabilized on the 6 to 7 per cent level. The fact that it is so low now should perhaps be recognized as a positive phenomenon; it seems to give evidence that magistrates, who but certainly conduct also preparatory proceedings, do not send cases too hastily for hearing where the juvenile’s guilt seems insufficiently made probable to them. It may be asked upon how many juvenile suspects educative-or correctional means are adjudicated following a finding of guilt. A summary of the data obtained from the police or court statistics may supply an answer. As was said before, cases of almost 60 per cent of suspected juveniles end up with a finding of guilt, that proportion being slightly lower in boys than in girls and in lower age groups rather than in older. Very few suspects of 7 to 9 years of age are found guilty (7 per cent). Those proportions increase rapidly already in 10 year-old suspects (47 per cent) and grow up to 13 yearsage-group (62 per cent) showing then a stabilization on a similar level. According to the information mentioned, in 1961-1967 annual numbers of findings of guilt were 27 to 38 thousand. Those numbers included, of course, a majority of findings of guilt by juvenile courts and also sentences of ordinary courts. The latter were concerned with cases when a juvenile was 17 years of age prior to the beginning of the hearing or when he or she acted together with an adult and when according to the prosecution’s decision “for the benefit of the administration of justice” their case should not be transferred to the juvenile court. The proportion of findings of guilt by ordinary courts of law was about 9 to 11 per cent in 1961-1967, having been slightly lower than in 1951-1960 when sometimes it reached even 13 per cent. This is probably connected with some lowering of the mean age of juveniles found guilty for the last few years as compared with that observed in 1951-1960. 4. The number of juveniles upon whom judicial.educative or correctional means had been executed provide information about another side of the quantitative aspect of work facing the juvenile courts. The number of juveniles under court control due to a committed offence increased from 34,520 in 1951 to 58,005 in 1967 and that is by 68 per cent. This seems to be an effect of not only an increase in the number of juveniles found guilty but also of a prolonged average duration of execution of means. That considerable number of juveniles upon whom means were executed should perhaps be further increased. So, for instance, in 1965 45.055 children and youth were placed under juvenile court control, established according to civil proceedings, and under ordinary court control there were another 23,699. As for some portion of the number of such juveniles, court control was certainly connected with manifestations of their social maladjustment, with behavioural disturbances not varying in nature from those for which other juveniles were found guilty. Also in some of those cases, the way of carrying out the control did not differ significantly from the means usually applied, such as supervision order, probation or approved school. 5. Since in the hitherto discussed ways of understanding the range of the detected juvenile delinquency the main stress was laid on absolute numbers, in the present analysis of the standards some attention may be paid to relative numbers resulting from a reference of the number of findings of guilt to some population of individuals concerned or of the number of juveniles found guilty to some broader population of which they were a portion. The objective of such an analysis is to illustrate the degree to which the phenomena of delinquency have been spread throughout the juvenile population. This will lead to quite a different manner of appreciating the juvenile delinquency range. It will not be considered weighty e.g., when the number of findings of guilt will reach some definite level but when the number of juvenile offenders in the juvenile population will be sufficiently high. The most common standard of that kind is represented by delinquency which, if applied for analysing data of court statistics with regard to juvenile delinquency, is represented by the number of findings of guilt as one pro mille of the entire juvenile population. As compared with absolute numbers, the above listed rates give the following picture: between 1961 and 1965, a slight (a few-per-cent) increase in the number of findings of guilt was observed, however, considering that this was accompanied by a much higher increase in the number of i0-16 year-old juveniles, the rates showed a decrease. During the following two years; there was a significant change of that situation, the increase in the number of findings of guilt was then so high that it brought about also an increase in rate values which in 1967 became 15 per cent higher than those in 1961. The increase in rates was by no means equal in all age groups of juveniles concerned, some were not involved at all. The rates in all age groups of girls were found on similar level as in 1956-1960. Thus, the increase in the number of findings of guilt in girls was proportional to the increase in the total population of 10-16 year-old girls. The annual average was one finding of guilt per 1,000 girls in that particular age group. With boys, the situation was different; here we had to deal with a general increase in rates as compared with that observed in the preceding five-year period. The increase in rates was very high in 14-16 year-old boys (by 19-23 per cent), approximate level was maintained in12-73 year-old boys and a decrease was observed in 10-11 year-old ones (by 5-10 per cent). An average rate of 196l-1967 for the total population of boys was 12,2 and showed that an annual average in the discussed seven-year period was one finding of guilt per 82 boys between 10 and 16 years of age. In our earlier discussion of the rank that the findings of guilt in juveniles held among the total number of such findings in 1961-1967, also young adults were mentioned. There were more findings of guilt in young adults although the latter belong only to four age groups (17, 18, 19 and 20) while the juveniles - to seven age groups at least. The above listed findings show first of all a systematic decrease in numbers of convictions in young adults (1961 -1964) followed, as compared with the 1961 level, by an increase (1965-1967) by 9 per cent in made and by 2 per cent in female offenders. This movement of absolute numbers of convictions in young adults was accompanied by simultaneous but considerable decrease in rates which although failing to increase after 1964, have maintained thę level of that year. Consequently, the relevant rates, as compared with 1961, were in 1967 - 30 per cent lower in men and 33 per cent in women. These changes were caused by a few independent agents whose effects were partially accumulated. Therefore it must be said that the rates in young men and women in 1961-1963 were on an approximate level. Its rapid decrease took place in 1964, which was undoubtedly connected with the Act of Amnesty of 20th July 1964 whose bearing on the number of convictions was certainly felt in 1965, too. At the same time, the effect of another diminishing agent was felt: according to the Decree of 28th March 1963, a certain number of young adults ceased to be subject to ordinary court proceedings since the conscription age limit was lowered to be 19 instead of 20 Years of age. In 1967, a successive agent appeared on the scene to have a bearing on the number of convictions in that category of individuals concerned (as well as of the adult population, too). Namely, in accordance with the provisions of the Decree of 17th June 1967, a series of minor offences were classified as non-indictable offences having at the same time become subject of administrative and not judicial proceedings; minor speculations or theft had been involved. As far as the rates were concerned, an additional element started functioning; it was a process of leaving the young adult age group by individuals born during the war (law quantity year groups) on one hand and of entering into that particular age of very numerous year groups of those born after the war, on the other. Prospectives for an extent of young adult convictions for the next few years to come should perhaps be worth while mentioning now. As a result of a thorough analysis of the young adult conviction rate in 1961-1965, of legislative changes and of foreseen changes in numbers of the total young adult population (which will still be increasing for another few years) - the author had drawn the following conclusion. In 1970, the number of convictions of male young adults will probably be about 38 thousand while the rate will reach about 28.0; the relevant figures for females will be 5.5 thousand and 4.0 respectively. In closing our remarks on an evaluation of juvenile and young adult known delinquency extent, made in terms of rates, it might be said that analogically to earlier rates based on the numbers of convictions, also other , rates" might be established, where data on numbers of juveniles on whom educative or correctional means had been executed by juvenile courts, could be utilized. A reference of the number of such juveniles to the total number of 10-16 year old ones would lead to the following findings: in 1961, they were 8.7 pro mille of all juveniles of 10-16 years of age but after 7 years - they were 11.8. Thus, as per 31st December 1967, out of each 86 juveniles of 10-16 years of age group, one was under a juvenile court control a subject of executed educative or correctional means. 6. So far, analyses of a degree, to which known juvenile delinquency had spread among youth, were based on information about findings of guilt, however, there is also a possibility to define it by reference to the number of juveniles found guilty. To do so, one has to know how many juveniles, out of those born during one calendar year were found guilty for offences committed by them at thęir juvenile age, exclusively between 11th and 17th years of age. By making use of the data on findings of guilt in 1950- 1960, one could see that for each year group of juveniles born in 1941, 1942, 1943 or 1944, the number of individuals found guilty were 14.1 to 14.9 thousand; their percentage, related to the total number of those born in the said year groups’ was 3.5 to 3.8 per cent (for boys only - 6.3 to 6.8 per cent). Thanks to the fact that complete data on findings of guilt have now been available for 1961-1967, an extention of the analysis with respect to few further year groups could be possible. As it may be seen, the numbers of juveniles found guilty, born in the successive years just after the war, increased rapidly (from about 15 to 28 thousand). That increase, however, took place with a simultaneous considerable increase in general quantities of those particular year groups. In the entire population of those of 17 years old, the percentage of juveniles found guilty was approximately on similar level (on a slightly.higher levęl than in the case of those born during the war). Although such a percentage was low in girls, in boys it grew up as high as 6,7 to 7,5 per cent. This means that approximately every thirteenth - fourteenth young adult of 17 years of age born between 1945 and 1951 had already been found guilty for an offence committed at his juvenile age. Analogical attempts to define the number of found guilty within some longer period of time, where findings of guilt could be referred to not only to one but to a sequency of years - in young adults - are more difficult than in juveniles. It is because of relevant shortage of statistics in Poland. By way of analysing data on convictions in 1951 -1963, I had defined some approximate number of young adults, born in 1939, 1940, 1941 and 1942, covicted, at whatever moment of the entire four-year period when they were young adults (between I7 and 20 years of age). In the population of 21 year-old men (born in the above mentioned years) there were about 15 per cent of those who had once been found guilty at their young adult age. This means that approximately every seventh man at that particular age had been convicted at his young adult age. Should the entire eleven-year period between 10th and 21st year of age be taken into account, one would have to accept that every sixth had been found guilty. The above mentioned figures seem very high, indeed. This calls for a thought to be given as to whether or not the penalization extent in this country is not too much expanded or whether or not penal means are too hastily applied when - without prejudice or even to some purpose - they could be given up. 7. So far, data of twofold nature were used for defining standards of known juvenile delinquency extent: numbers of individuals (found guilty) or numbers of events, such as findings of guilt, adjudgements or cases in which a juvenile was a suspect. Let us mention another type of dates which in its character is approximate to the latter category: numbers of offences where juveniles were suspects. Relevant information is provided for by police statistics. According to data of that kind, numbers of offences where juveniles were suspects were 99,588 in 1956 and 110,892 in 1967. 8. Also various ways of interpretation of known juvenile delinquency extents as well as various standards of such extents were discussed. In dealing with legal order endangered by juveniles, attention will first of all be paid to the numbers of offences where juveniles were suspects, especially, so if that standard would adequately be enriched by data concerning the kind or importance of such offences. If interest is taken in quantitative aspects of tasks facing ouf courts of law, the juvenile delinquency extent will be looked at through a prism of the number of adjudgements (especially - of findings of guilt) as well as of the number of subjects under the juvenile court control due to execution of educative or correctional means adjudicated. In that particular area, the extent of juvenile delinquency for the recent seven-year period considerably increased, what might to a certain degree be related to a general increase of the youth population in this country in that period. If one wants to know the degree to which manifestations of known to the police major juvenile depravity has bęen spread, delinquency rates should be used or - what even allows for a broader look at that problem - the percentage of those found guilty for offences committed at their juvenile age in relation to the young adult population born in particular year groups. The abovementioned rates as well as - though to a minor extent - the percentages seem to show that the known juvenile delinquency in this country increased, especially for the last few years. 3. A definition of the delinquency structure is usually understood to include the elements delinquency is composed of and the numerical ratio of delinquency groups differentiated either from delinquency as a whole or from its particular categories. If so understood, in analysing the delinquency structure it is only natural to use a body of information in which offence is a unity. This may be data on the total number of offences committed in a selected area at a certain definite time, irrespective of the method of its evaluation; this may also be a body of data on known offences, on offences where a suspect had been determined in the course of preparatory proceedings or, finally, a body of information about offences where offenders had lawfully been convicted or found guilty. In most cases no such data are available (except perhaps for the second of the mentioned bodies of information which is a fundamental section of police statistics). However, where interest is taken in the delinquency structure, related to a definite category of offenders - to juveniles, the analyser is as a rule compulsed to search for material of different kind. Such material would usually include data on findings of guilt, enriched as they are with information about the nature of offences concerned. An analysis of such data leads to the following conclusions: A considerable increase in the number of findings of guilt in 1961-1967 failed to produce any substantial changes of the juvenile delinquency structure. It is still offences against property (86 to 89 per cent) which are dominant in juvenile delinquency - mostly including theft of things of minor value. Besides, a somewhat numerous group embraced offences against the person (5 to 7 per cent), in which slight bodily harm (about 1/3 of cases), assault (1/5 of cases) and battery or grievous bodily harm dominated. Annually, there were 5 to 11 juveniles found guilty for murder and 21 to 35 for manslaughter. In 7967,614 juveniles were found guilty for sexual offences (1.7 per cent of the total number of findings of guilt in that very year); rape was found in more than a half of cases, the remaining ones having been fornication with juveniles below 15 years of age. About one per cent of cases included offences against public order officers. Offenders of other categories were few. A higher than average increase in the number of findings of guilt for housebreaking or burglary, for damage done to property, a series of offences against the person and for rape has been noted since 1961. This was accompanied by an increase of the mean age of juveniles found guilty annually - from 13,8 years in 1961 to 14,3 years in 1967. It is no wonder then that first of all an increase in the proportion of offences committed by juveniles of older year groups has been observed. A peculiarity of the.juvenile delinquency structure becomes clearly-cut, indeed, when compared with the young adult and adult delinquency structures. Differentiation of only 4 delinquency groups (against property, against the person, sexual offences and those against public order officers) is sufficient to embrace a) almost the entire juvenile delinquency (93 to 96 per cent), b) a considerable proportion of young adult ddlinquency and c) but only below 60 per cent of adult delinquency. The fact that a great majority of juvenile delinquency are related to offences against property (chiefly theft) of minor importance must by no means stipulate that such a delinquency should be neglected. On the contrary, the effects of commitments of various, often slight, offences turn out too often to be serious. This may not be clear when only single cases are considered but when the developing process of juvenile social depravation is taken into account whose that sort of offerences are but a fragment only. According to findings of individual studies, the extent of juvenile offenders demoralization shows either a slight or no connection with the objectively evaluated specific gravity of offences ascribed to juveniles. 4. The activities of juvenile courts or of ordinary courts of law with regard to the adjudication of educative or correctional means upon juveniles in 1951-1967 was the last question discussed in the study. A salient feature of the adjudication by our courts upon juveniles is their very considerable caution in applying means connected with separation of a juvenile from his or her familial community and sending them to an institution. The percentage of juveniles upon whom approved school or borstal had been adjucated was between 10 and 14 per cent, in recent years having been stabilized as l0 to 11 per cent. From that fact a conclusion can hardly be drawn that it was only every 9th or 10th juvenile upon whom an institutional order was considered necessary. Because it should always be remembered that the adjudication in that particular subject is influenced not only by an evaluation of the degree of juvenile social depravity, of educational valours represented by the juveniles’ environment, of needs of the juvenile’s himself, but also by the realistic possibility of execution of such an adjudication since there is chronic lack of placements in approved schools and very often felt lack of placements in borstals. With respect to further 15 to 24 per cent of juveniles found guilty, eventual need for applying institutional treatment must have been felt by the courts since executions of relevant adjustications had been suspended and 3/4 of cases were placed on probation. Probation was the most frequently applied means with respect to juveniles. That particular means was applied almost in 1/3 of all juveniles found guilty, the proportion of such adjudications having considerably increased in 1951-1967, i.e from 23.2 per cent to 32.2 per cent, so that the yearly number of juveniles placed on probation augmented threefold. Supervision order is another kind of means which used to be more frequently adjudicated early in the fifties and now it is adjudicated upon every 4th-5th juvenile. Most probably, the observed changes regarding preference of adjudication of probation is caused by development of such services enabling probation of increased numbers of juveniles found guilty. Admonition was a mean whose application seemed to be decreasing (it was adjudicated upon 23 per cent of juveniles in 1951 and only upon 14 per cent in 1967). A rapid decrease in the number of juveniles upon whom the courts were satisfied by applying that particular single act a few years after 1951, was probably due to a simultaneous rapid growth of the mean juvenile defendant age progressing according to a rise of the age limit of juvenile responsibility from 7 to 10 years of age (1954). On the other hand, the recently observed considerable decrease in proportion of such adjudications is undoubtedly closely connected with advising the courts in terms of limitation of means to be adjudicated upon juveniles of younger year groups. The choice of adequate educative or correctional means was no doubt influenced not only by the court having been convinced as to which was the best mean for the juvenile’s re-education but also what were the realistic possibilities to get the mean executed. An open question is to what extent the changes of the structure of adjudicated means are a result of changes in categories of juveniles appearing at the courts.